2018
DOI: 10.1186/s12890-018-0695-4
|View full text |Cite
|
Sign up to set email alerts
|

Balloon pulmonary angioplasty – efficient therapy of chronic thromboembolic pulmonary hypertension in the patient with advanced sarcoidosis – a case report

Abstract: BackgroundApproximately a quarter of patients with advanced sarcoidosis develop pulmonary hypertension (PH), which affects their prognosis. We report unusual case of confirmed chronic thromboembolic pulmonary hypertension (CTEPH) in a patient with stage IV sarcoidosis successfully treated with balloon pulmonary angioplasty (BPA).Case presentationA 65 years old male with a history of colitis ulcerosa, and pulmonary sarcoidosis diagnosed in 10 years before, on long term oral steroids, with a history of deep vein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…In situ thrombosis and venous thromboembolic disease (VTE) are other mechanisms of intrinsic pulmonary artery obstruction described in sarcoidosis patients [ 13 , 21 , 32 , 36 ]. VTE is more frequent in sarcoidosis compared to the general population, thus chronic thromboembolic pulmonary hypertension (CTEPH) as the cause of SAPH has to be also considered [ 23 , 32 , 33 , 37 , 38 ]. Several recently published studies have reported a twofold to fourfold increased risk of VTE in sarcoidosis patients compared to controls [ 36 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In situ thrombosis and venous thromboembolic disease (VTE) are other mechanisms of intrinsic pulmonary artery obstruction described in sarcoidosis patients [ 13 , 21 , 32 , 36 ]. VTE is more frequent in sarcoidosis compared to the general population, thus chronic thromboembolic pulmonary hypertension (CTEPH) as the cause of SAPH has to be also considered [ 23 , 32 , 33 , 37 , 38 ]. Several recently published studies have reported a twofold to fourfold increased risk of VTE in sarcoidosis patients compared to controls [ 36 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In case of active disease, corticosteroid and immunosuppressive treatment, are recommended [ 31 , 41 ]. Otherwise, balloon pulmonary angioplasty, which is currently recommended for the therapy of inoperable chronic thromboembolic pulmonary hypertension, or pulmonary artery stenting performed in PH expert centre may be considered [ 23 , 42 – 44 ]. In case of failure or insufficient response to treatment and deterioration of lung function, early referral for lung or lung and heart transplantation is recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rarely but importantly, mechanical interventions for nodal compression or fibrosing mediastintis including stenting of the PA [60] or vein [26] (often associated with a unilateral pleural effusion) may be required, however, these come with considerable risk. Pulmonary endarterectomy [61] and BPA [62] may be needed for associated CTEPH. Some patients with SAPH require lung transplantation, where although severe SAPH transplants are high risk and require veno-arterial extracorporeal membrane oxygenation support, longer term survival is not impacted by a pretransplant severe PH phenotype [63 ▪▪ ].…”
Section: Treatmentmentioning
confidence: 99%
“…Moreover, sarcoidosis is associated with increased risk of venous thromboembolism, which carries associated risk of developing CTEPH in some patients ( 97 , 98 ). Sarcoidosis can be associated with mediastinal and hilar lymphadenopathy that can cause extrinsic compression of pulmonary arteries (and venous stenosis) or fibrosing mediastinitis, resulting in SAPH.…”
Section: Pulmonary Hypertension In Sarcoidosismentioning
confidence: 99%